Efficient Allocation of Labor Maximizes Brood Development and Explains Why Intermediate-Sized Groups Perform Best During Colony-Founding in the Ant, Pogonomyrmex californicus - Shaffer, Zachary J.; Dreyer, Sara; Clark, Rebecca M.; Pratt, Stephen C.; Fewell, Jennifer H. (Frontiers in Ecology and Evolution, 2022)
While most cases of cooperation in nature occur between relatives, cooperation can also occur between unrelated individuals, requiring significant benefits to outweigh the costs of helping non-kin. This paper describes cooperation between unrelated queens of the ant, Pogonomyrmex californicus, during colony foundation. Referred to as pleometrosis –this cooperative phenomenon naturally invites questions surrounding the value of different group sizes. While previous studies have shown that pleometrosis improves queen survival and worker production, little work has been done to examine the precise behavioral interactions within nests that explains these advantages. Our study aimed to determine how the optimal group size for a small, simple social group is related to group productivity and the organization of work within the group. Collecting queens from a known pleometrotic population, we established nests with either 1, 3, 6, or 9 foundresses and observed the resulting nascent colonies for 50 days. We found that queens in social founding groups survived longer and had higher productivity. While all social groups were equally successful in producing workers, we found that intermediate-sized groups were most successful in terms of per capita production. Inactivity increased with group size. In addition, the proportion of essential colony growth tasks performed (such as foraging and brood care) was lowest in both solitary-founded groups and in groups of 9 queens. As a result, intermediate sized groups outperformed both solitary queens and groups of 9 in the efficiency with which they converted eggs into workers. These results emphasize the benefits of cooperation and the ways in which group size can influence fitness and the allocation of labor in social groups.